(untitled) (Philological Studies, 2019)
This paper focuses on certain aspects of the customs and beliefs related to house building in Macedonian and Polish culture, respectively. Special attention is paid to the initial part of building a house, which practically begins with the selection of construction materials and construction workers. The care that goes in providing good materials for the construction, as well as the concern for choosing quality workers, in both cultures, ensures a successful building of a house that would become a happy dwelling for its tenants.The analysis shows an analogy between the Macedonian and Polish construction traditions, respectively